Severity Of Ocular Findings In Different Types Of Leprosy In Relation To Its Duration - Keshri Pradip Kumar; Pathak Ashok; Kar H K; Sinha T R D (Wolters Kluwer Medknow Publications, 1999)
A study on 400 patients of leprosy was carried out to assess the ocular involvement in different types of leprosy. It was seen that duration of leprosy is one of the important factors responsible for the severity of ocular involvement. Early diagnosis and proper care have been stressed.